Quiet-time Pc 5 pulsations in the Earth's magnetotail: IMP-8, ISEE-1 and ISEE-3 simultaneous observations - D. V. Sarafopoulos; E. T. Sarris (Annales Geophysicae, 1994)
Quasi-periodic Pc 5 pulsations have been reported inside and just outside the Earth's magnetotail during intervals of low geomagnetic activity. In order to further define their characteristics and spatial extent, we present three case studies of simultaneous magnetic field and plasma observations by IMP-8, ISEE-1 (and ISEE-2 in one case) in the Earth's magnetotail and ISEE-3 far upstream of the bow shock, during intervals in which the spacecraft were widely separated. In the first case study, similar pulsations are observed by IMP-8 at the dawn flank of the plasma sheet and by ISEE-1 near the plasma sheet boundary layer (PSBL) near midnight local time. In the second case study, simultaneous pulsations are observed by IMP-8 in the dusk magnetosheath and by ISEE-1 and 2 in the dawn plasma sheet. In the third case study, simultaneous pulsations are observed in the north plasma sheet boundary layer and the south plasma sheet. We conclude that the pulsations occur simultaneously throughout much of the nightside magnetosphere and the surrounding magnetosheath, i.e. that they have a global character. Some additional findings are the following: (a) the observed pulsations are mixed mode compressional and transverse, where the compressional character is more apparent in the close vicinity of the plane ZGSM=0; (b) the compressional pulsations of the magnetic field in the dusk magnetosheath show peaks that coincide (almost one-to-one) with similar peaks observed inside the dawn plasma sheet; (c) in the second case study the polarization sense of the magnetic field and the recurrent left-hand plasma vortices observed in the dawn plasma sheet are consistent with anti-sunward moving waves on the magneto-pause; (d) pulsation amplitudes are weaker in the PSBL(or lobe) as compared with those in the magneto-tail's flanks, suggesting a decay with distance from the magnetopause; (e) the thickness of the plasma sheet (under extremely quiet conditions) is estimated to be ~22 RE at an average location of (X, Y)GSM=(16, 17) RE, whereas at midnight local time the thickness is ~14 RE. The detected pulsations are probably due to the pressure variations (recorded by ISEE-3) in the solar wind, and/or the Kelvin Helmholtz instability in the low-latitude boundary layer or the magnetopause due to a strongly northward IMF.